Suita za mali orkester (1932) Demetrija Žebreta med "starimi" in "novimi" strukturnimi idiomi - Salmič Kovačič, Karmen (Muzikološki zbornik, 2007)
Demetrij Žebre's Suite for Small Orchestra (1932) is his only orchestral work composed during his period of study with Slavko Osterc and the first piece worthy of extended analysis considering its parodical/satirical nature. With this presented analysis and by the discussion of paticular structural parameters, it will be possible to define the older compositional idioms from the newer or more artistic categories of the style which later became a part of Žebre's orchestral opus. Among these categories are his developments of rhythm and melody, his use of incongruous meters, vertical and horizontal combined metrics, fuller orchestration, new approaches to tonality, chords and layers, singular use of mono thematics and the use of multi structuring in the longer symphonic phrase.
Keywords: 20.st.; slovenska sodobna glasba; Žebre, Demetrij, 1912-1970; Žebre, Demetrij: Suita za mali orkester